How do you find the axis of symmetry, vertex and x intercepts for #y=-3x^2+6x+1#?

Answer 1

#"vertex": (1, 4)#, #"axis of symmetry": x = 1#
#x-"intercepts": (1-(2sqrt(3))/3, 0), (1+(2sqrt(3))/3, 0)#

To find the vertex and axis of symmetry: Put the equation in standard form: #y = a(x-h)^2 + k#, where axis of symmetry :# x = h# and #"vertex" = (h, k)#
First factor the #x# terms: #y = -3(x^2 -2x) + 1 #
Use completing of the square: 1. Multiply the #x#-term coefficient by #1/2# to get the completed square constant: #1/2 * -2 = -1# 2. Write the completed square: #(x -1)^2 = x^2 - 2x + 1# 3. Add the #x^2 #coefficient: #-3(x -1)^2 = -3x^2 +6x -3#. 4. Notice from step 3, an extra constant was added when completing the square: #-3#. This will need to be subtracted to keep the equation the same as the original equation: #y = -3(x -1)^2 + 1 -(-3)# 5. #y = -3(x -1)^2 + 4 #
#"vertex": (1, 4)#, #"axis of symmetry": x = 1#
To find #x#-intercepts: Use the quadratic equation since factoring isn't simple. Put the equation in the form: #Ax^2 + Bx +C = 0#
#x = (-B +- sqrt(B^2 - 4AC))/(2A) = (-6 +- sqrt(36-4(-3)(1)))/(2(-3))#
#x = (-6+- sqrt(48))/(-6) = 1 +- (4sqrt(3))/-6 = 1 +-(2sqrt(3))/-3#
#x-"intercepts": (1-(2sqrt(3))/3, 0), (1+(2sqrt(3))/3, 0)#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

Please see the explanation.

When given a quadratic of the form: #y = ax^2+bx+c#
The equation for axis of symmetry is: #x=-b/(2a)#

The x coordinate of the vertex, h, is the same as the axis of symmetry:

#h = -b/(2a)#

The y coordinate of the vertex, k, is the function evaluated at h:

#k = y(h)#

The x intercepts can be found by factoring or by using the quadratic formula:

#x = (-b-sqrt(b^2-4(a)(c)))/(2a)# and #x = (-b+sqrt(b^2-4(a)(c)))/(2a)#
Now, to the given equation: #y = -3x^2+6x+1#
Please observe that #a = -3, b = 6, and c = 1#

The computation for the axis of symmetry is as follows:

#x = -b/(2a)#
#x = -6/(2(-3))#
#x = 1 larr# the equation for the axis of symmetry.

The x coordinate of the vertex, h, is the same as the axis of symmetry:

#h = 1#

The y coordinate of the vertex, k, is the function evaluated at h:

#k = y(1)= -3(1)^2+6(1)+1#
#k = 4#
The vertex is the point #(1,4)#
As a prelude to finding the x intercepts, compute #b^2-4(a)(c)#:
#6^2-4(-3)(1) = 36+12 = 48#

Because 48 is a positive real number, we know that there are two distinct roots and, because 48 is not a perfect square, we know that the quadratic will not factor.

Therefore, we find x intercepts using the quadratic formula:

#x = (-b-sqrt(b^2-4(a)(c)))/(2a)# and #x = (-b+sqrt(b^2-4(a)(c)))/(2a)#
#x= (-6-sqrt(48))/(2(-3))# and #x= (-6+sqrt(48))/(2(-3))#
#x= 1-sqrt(48/36)# and #x= 1+sqrt(48/36)#
#x= 1-sqrt(4/3)# and #x= 1+sqrt(4/3)larr# x intercepts
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 3

Axis of symmetry: ( x = \frac{-b}{2a} = \frac{-6}{2*(-3)} = 1 )

Vertex: Substitute ( x = 1 ) into the equation to find the y-coordinate: ( y = -3(1)^2 + 6(1) + 1 = 4 ) Vertex is at ( (1, 4) )

To find x-intercepts: Set ( y = 0 ) and solve for ( x ) using the quadratic formula: [ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} ] [ x = \frac{-6 \pm \sqrt{6^2 - 4*(-3)1}}{2(-3)} ] [ x = \frac{-6 \pm \sqrt{36 + 12}}{-6} ] [ x = \frac{-6 \pm \sqrt{48}}{-6} ] [ x = \frac{-6 \pm 4\sqrt{3}}{-6} ] [ x = 1 \pm \frac{2\sqrt{3}}{3} ]

The x-intercepts are ( x = 1 + \frac{2\sqrt{3}}{3} ) and ( x = 1 - \frac{2\sqrt{3}}{3} ).

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7